New nanobidentate Schiff base ligand of 2-aminophenol with 2-acetyl ferrocene with some lanthanide metal ions: synthesis, characterization and Hepatitis A, B, C and breast cancer docking studies. Issue 20 (18th October 2017) - Mahmoud, Walaa H.; Mahmoud, Nessma F.; Mohamed, Gehad G.
Abstract: Three lanthanide complexes (La(III), Er(III), and Yb(III)) derived from ferrocene-based Schiff base ligand (HL) were synthesized from condensation of 2-aminophenol with 2-acetylferrocene. The ligand and metal complexes were characterized based on elemental analyses, IR, 1 H NMR, molar conductance, SEM and thermal analyses (TG, DTG). The molar conductance revealed that all the metal chelates were electrolytes having the general composition [M(L)(Cl)(H2 O)3 ]Cl·4H2 O. HL and its complexes were screened for their antibacterial and antifungal activity by agar diffusion method. The results of these studies showed that the metal complexes are more effective antibacterial and antifungal agents as compared with the free ligand. The anticancer activity was screened against human breast cancer cell line (MCF-7). Results indicated that metal complexes showed an increased cytotoxicity in proliferation to cell lines as compared to free ligand. Molecular docking studies were performed to identify the binding orientation or conformation of a complex in the active site of the protein. HL and its complexes were docked with crystal structure of DDB1 of breast cancer, crystal structure of HCV, RNA-dependent RNA polymerase, receptors of HBV core protein, crystal structure of the Fab fragment of anti-HAV. Abstract :